Patient profiles and clinical utility of mepolizumab in severe eosinophilic asthma - Haldar P (Dove Medical Press, 2017)
Pranabashis Haldar Respiratory Biomedical Research Unit, Glenfield Hospital, University of Leicester, Leicester, UK Abstract: Mepolizumab (Nucala®) is an effective and specific anti-eosinophil molecular therapy that has recently been approved as add-on therapy for the management of severe eosinophilic asthma by the US Food and Drug Administration (FDA), European Medicines Agency (EMA; European Union) and more recently National Institute for Health and Care Excellence (NICE; UK). It is one of several molecular therapies in development for this indication and is illustrative of the strategic trajectory for pharmaceutical drug development taken over the past decade in several disease areas. Molecular therapies offer the prospect of improved specificity and effectiveness of biological effect. However, this necessitates a clear understanding of the underlying mechanistic pathways underpinning pathological processes, to inform drug development that yields novel more efficacious treatment options with a better clinical profile than existing agents. For the first time, utilization of molecular therapies in clinical trials is providing a novel in vivo model to characterize the association between specific pathways and clinical disease expression. It is increasingly recognized that asthma exhibits both clinical and pathological heterogeneity. It follows that a one-size-fits-all approach will not be appropriate and cost-effectiveness may only be achieved by identifying responder subgroups. This so-called personalized approach to therapy is being supported by the parallel development of companion biomarkers for clinical application. In this review, the author summarizes the clinical studies, their interpretation and the lessons learnt with mepolizumab that have informed our understanding of the approach to personalized molecular therapy in asthma. Keywords: IL-5, Nucala, exacerbations